A Generative Phonology: Syllable Structure of Hajji Yemeni Arabic - Jubran AL-Mamri, Muhammed (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2023)
This study deals with the syllable structure of Hajji Yemeni Arabic (HYA) in the light of Generative Phonology. Hajji Yemeni Arabic is a variation of Arabic spoken in the northwestern part of Yemen, which tries to elaborate and discuss the elements of syllable structure and possibilities of patterns of syllables in a term of consonants and vowels. The main aim of this study is to investigate the syllabification patterns of Hajji Yemeni Arabic, hereafter referred to as (HYA). Through qualitative phenomenology, this study analyzed the different syllabification patterns attested in Hajji Yemeni Arabic and a comprehensive analysis of the syllable shape within the framework of Generative Phonology. The findings of the study; Hajji Yemeni Arabic has five patterns of syllables: (monosyllabic, disyllabic, trisyllabic, tetrasyllabic and pentasyllabic). Hajji Yemeni Arabic prohibits initial consonant clusters, but consonant clusters are permitted in the coda position, and the maximum number of permitted consonants is two only. No vowel occurs word-initially, and every syllable must begin with one and only one consonant sound (simple onset). Hajji Yemeni Arabic has two kinds of syllables: open syllables, as in the syllable shapes /CV/ and /CV:/, while closed syllables, as in the syllable shapes /CVC/, /CV:CC/, /CV:C/ and /CVCC/.